Poverty reduction in Upper West Region, Ghana: role of the Livelihood Empowerment Against Poverty programme. Issue 6 (18th August 2019) - Fuseini, Moses Naiim; Enu-Kwesi, Francis; Sulemana, Mohammed
ABSTRACT: The Livelihood Empowerment Against Poverty (LEAP) programme was established in Ghana to tackle poverty, yet studies on LEAP yielded inconclusive results on its effects. This article reports on an assessment of the effects of LEAP on poverty reduction, using an "after-only" study design. Results suggest that beneficiaries saw improvement in food consumption, income levels, savings levels, access to healthcare, and school attendance following participation in LEAP. The study concludes that LEAP contributed to poverty reduction as it enhanced beneficiaries' living conditions. It recommends that LEAP targeting be based on the Ghana National Household Registry's database to eliminate inclusion errors.